2014
DOI: 10.1007/s12667-014-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of spatial distribution when analysing the impact of electric vehicles on voltage stability in distribution networks

Abstract: The recent emergence of distributed generation, smart meters, and electric vehicles means that much attention is now being given to network modelling and analysis at the distribution, rather than transmission, level.Many optimisation studies, both regarding technical and economic questions, aim to satisfy the constraints posed by grid infrastructure. We explore in detail

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…All data input/output, logging, and algorithmic charging decisions are conducted using POSSIM. 3 More detailed descriptions of the simulation and modelling process are provided in de Hoog, Muenzel et al (2014).…”
Section: Modeling the Last Mile Of The Networkmentioning
confidence: 99%
“…All data input/output, logging, and algorithmic charging decisions are conducted using POSSIM. 3 More detailed descriptions of the simulation and modelling process are provided in de Hoog, Muenzel et al (2014).…”
Section: Modeling the Last Mile Of The Networkmentioning
confidence: 99%
“…The degradation of voltage profile, increase in peak load, harmonic distortions are some of the consequences of the uncoordinated charging of EVs. Many references demonstrate the adverse impact of EV charging loads on different parameters of the distribution network like voltage profile [8][9][10][11][12][13][14], harmonics [15][16][17][18] and peak load [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of EV charging loads on the voltage stability of distribution network was also analysed in [11][12][13][14]. From the findings of [11][12][13][14], it is observed that most of the distribution networks could withstand the penetration of EVs up to a certain level. However, networks designed a decade ago are not equipped to withstand any large-scale integration of EVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5] is proposed a mixed-integer optimization model to decide between centralized and decentralized generation sources for new energy infrastructure development. In [6] is demonstrated that the physical locations of individual loads in the network (focus in electric vehicle charging) can determine if voltages values throughout the network remain in the required limits. In are presented methodologies to use DGs as an active element on technical planning process, i.e., DGs are used as a part of technical planning solution, through DGs optimal placement in the electrical distribution network.…”
Section: Introductionmentioning
confidence: 99%